Effect of Propolis Extract on Biodistribution of Sodium Pertechnetate (Na99mTcO4) - Holanda, Cecília Maria de Carvalho Xavier; Barbosa, Vanessa Santos de Arruda; Rodrigues, Yullyanna Moreira; Saraiva, Eider Maia; Demeda, Vanessa Fávero; Medeiros, Hilkéa Carla Sousa de; Açucena, Maria Kadja Meneses Torres; Sampaio, Tarciso Bruno Montenegro; Medeiros, Aldo da Cunha (JOURNAL OF SURGICAL AND CLINICAL RESEARCH, 2014)
Objective: Propolis is a bee product useful natural substance applied in medicine. We have investigated the effect of propolis extract on biodistribution of sodium pertechnetate (Na99mTcO4)and laboratorial parameters in rats. Methods: It was administered, by gavage, 1.0ml/day of propolis into 10 rats (treated group) during 10 days and 1.0 ml/day of saline solution into other 10 rats (control group), by the same via and period. On the 10th day, after 60min, all the animals received 0.1ml of Na99mTcO4 by ocular via. 50% of each group of rats was killed after 10min and other 50%, after 30min. Samples of brain, stomach, small bowel, liver, kidneys, thyroid and lungs were isolated and the %ATI/g of each organ was calculated. Tissue samples were taken from all the organs and stained by HE and PAS. Data were compared by Mann–Whitney and Student’s t-tests (p<0.05). Results: There was a statistically significant increase in the %ATI/g, from control to treated group, respectively, in small bowel (0.15±0.01 to 0.32±0.09, after 10min and 0.32±0.03 to 0.42±0.02, after 30min) and blood (0.22±0.01 to 0.48±0.02, after10min and 0.38±0.02 to 0.51±0.04, after 30min).Conclusion: Propolis extract facilitated the uptake of Na99mTcO4 in some organs of rats and increased levels of some laboratorial parameters. Keywords: Propolis. Herbal Medicine. Sodium Pertechnetate Tc 99m. Radiopharmaceuticals.Rats